The Moderator Effect of Internal Control System on the Relationship between Environmental Turbulence and Firm Performance in Jordanian listed companies - Ershaid, Diala Jehad; Abdullah, Akilah; Mohamed, Mudzamir (2017)
Objective: The purpose of this paper is to investigate the impact of environmental turbulence on firm performance of listed companies in Jordan.A conceptual model is proposed in this paper where firm performance is expected to be influenced by a two-dimensional environmental turbulence factor (technological turbulence and market turbulence) with a moderating factor of internal control system.Proposed Method: A questionnaire survey would be administered to 253 listed companies in Amman stock Exchange and analysis could be done with Partial Least Square (PLS) for testing the hypotheses of the study that firm performance is being influenced by environmental turbulence with a moderating effect of internal control system.Expected Results: It expected that when this proposed conceptual model is used with empirical data, the result of the research will provide a good understanding of the influence of the two environmental turbulence factors (technology and market) on firm performance of Jornadian listed companies.The result will also highlight the extent of the moderating effect of internal control system on the relationship between environmental turbulence and firm performance. Implication: Even though this research paper only presents a conceptual framework, but it proposes an aspect that needs to be tested with empirical data among Jordanian listed companies because of their significance in the business environment and the Jordan’s economy as a whole.The study is also of particular importance to the management of listed firms in knowing the moderating role of their internal control system on the relationship between the environmental turbulence and firm performance